1975
DOI: 10.2527/jas1975.413819x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prepartum Nutrition on the Reproductive Performance of Beef Females and the Performance of Their Progeny

Abstract: Two experiments were designed to assess the importance of maternal nutrition in the later stages of gestation on reproductive performance of beef females and on the growth and survival of their calves. In experiment 1, 59 Hereford first-calf heifers were assigned to one of two levels of dietary energy (high [HI which was 100% of the recommended level of prepartum energy or low [L] which was 65% of the N.R.C. [1970] recommended level) 100 days prior to predicted calving. After calving both groups were fed N.R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
106
8
8

Year Published

1986
1986
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(138 citation statements)
references
References 5 publications
16
106
8
8
Order By: Relevance
“…Variation in feed energy available to the dam during this period resulted in differences in birth weight, ranging from 0 to 8.2 kg (Dunn et al, 1969;Tudor, 1972;Laster, 1974;Corah et al, 1975;Bellows and Short, 1978;Kroker and Cummins, 1979;Bellows et al, 1982). Similarly, variable protein supply of the diet during the third trimester may or may not (Anthony et al, 1986a;Holland and Odde, 1992) alter birth weight of calves, while restricted or supplemental dietary protein during early or mid-pregnancy had little effect on birth weights (Perry et al, 1999 and.…”
Section: Intrauterine Growth Retardationmentioning
confidence: 99%
“…Variation in feed energy available to the dam during this period resulted in differences in birth weight, ranging from 0 to 8.2 kg (Dunn et al, 1969;Tudor, 1972;Laster, 1974;Corah et al, 1975;Bellows and Short, 1978;Kroker and Cummins, 1979;Bellows et al, 1982). Similarly, variable protein supply of the diet during the third trimester may or may not (Anthony et al, 1986a;Holland and Odde, 1992) alter birth weight of calves, while restricted or supplemental dietary protein during early or mid-pregnancy had little effect on birth weights (Perry et al, 1999 and.…”
Section: Intrauterine Growth Retardationmentioning
confidence: 99%
“…Also, the percentage of live calves at weaning was greater for HBCS, averaging 99% and 88% for HBCS and LBCS cows, respectively (P = 0.01). A reduction in live calves at weaning caused by nutrient restriction (Corah et al, 1975) or a lack of supplementation (Stalker et al, 2006) during the last trimester of gestation has been reported. However, like Stalker et al (2007) we did not observe an effect of supplementation on live calves at weaning.…”
Section: Calf Performancementioning
confidence: 99%
“…However, in a few studies cow nutrition has been linked to calf mortality (e.g. when cows were kept on an energyrestricted diet during late gestation leading to reduced birthweight; Corah et al 1975).…”
Section: Animal Behaviour and Welfarementioning
confidence: 99%